Shape memory polyurethane foams - B. K. Kim; S. M. Kang; S. J. Lee (eXPRESS Polymer Letters)
Molded flexible polyurethane (PU) foams have been synthesized from polypropylene glycol (PPG) with different molecular weights (Mw) and functionalities (f), and 2,4/2,6-toluene diisocyanate (TDI-80) with water as blowing agent. It was found that the glassy state properties of the foam mainly depended on the urethane group content while the rubbery state properties on the crosslink density. That is, PPG of low MW and low f (more urethane groups) provided superior glass state modulus, strength, density, shape fixity and glass transition temperature (Tg), while that of high Mw and high f (higher crosslink density) showed high rubbery modulus and shape recovery. Consequently shape fixity of low Mw PPG decreased from 85 to 72% while shape recovery increased from 52 to 63% as the content of high Mw PPG increased from 0 to 40%.